Sickle Cell Disease - Pain and Common Chronic Complications 2016
DOI: 10.5772/64917
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Transplantation in Patients with Sickle Cell Disease

Abstract: Hematopoietic stem cell transplantation (HSCT) is currently the only established cure for sickle cell disease (SCD). Replacement of the stem cell that has the defective beta globin allele with the normal gene decreases hemoglobin S and the risk of complications of SCD. The irst case reported was a girl with acute myeloid leukemia and SCD who received HSCT and achieved long-term SCD and leukemia-free survival. Given the favorable outcomes of HSCT with thalassemia major using myeloablative preparative regimens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Transplant has been performed, for the most part, in patients who have suffered a stroke, have had multiple episodes of acute chest syndrome, or have had recurrent vaso-occlusive crises (≥3 episodes requiring hospitalization per year), ie, patients considered to have the worst disease severity. 125 Controversies have arisen not only about whom to transplant but also about the optimal age to transplant, source of donor cells, and type of conditioning regimen. [126][127][128][129][130] Most stem cell transplants thus far have relied upon myeloablative conditioning regimens and have been bone marrow-derived with human leukocyte antigen (HLA)matched sibling donors as the source of stem cells.…”
Section: Cures For Sickle Cell Disease Stem Cell Transplantationmentioning
confidence: 99%
“…Transplant has been performed, for the most part, in patients who have suffered a stroke, have had multiple episodes of acute chest syndrome, or have had recurrent vaso-occlusive crises (≥3 episodes requiring hospitalization per year), ie, patients considered to have the worst disease severity. 125 Controversies have arisen not only about whom to transplant but also about the optimal age to transplant, source of donor cells, and type of conditioning regimen. [126][127][128][129][130] Most stem cell transplants thus far have relied upon myeloablative conditioning regimens and have been bone marrow-derived with human leukocyte antigen (HLA)matched sibling donors as the source of stem cells.…”
Section: Cures For Sickle Cell Disease Stem Cell Transplantationmentioning
confidence: 99%
“…is study also reported promotion and educational programmes are needed in order to increase the public awareness on SCD and the value of Premarital Screening (PMS) [34]. A study conducted in Oman shows that Hematopoietic stem cell transplantation (HSCT) improves organ function, quality of life, and facilitates disease-free survival [35]. ough, nonnursing interventions supports the improvement of HRQOL of children with SCD, no nurse-led, culturally-tailored, interventional studies have been conducted in Oman in order to improve the HRQOL of Omani children.…”
Section: Discussionmentioning
confidence: 99%